Diseño e implementación de un sistema para el control y monitoreo de equipos y sistemas productivos que permita obtener de forma automática la Eficiencia Global de la Mano de Obra (OLE) - Hidalgo-Pérez, Carlos Daniel (Instituto Tecnológico de Costa Rica, 2014)
The project consist in the "Design and Implementation of a system that automatically provides the Global Efficiency Workforce (OLE) by controlling and monitoring equipment and production systems”, developed at Panduit Costa Rica. The methodology used is the "engineering design process" which involves: defining the problem; obtaining relevant information; generating different solutions; analysis and selection of the solution; and testing and implementing the solution. In addition, we must recognize what extent are industrial processes and visualize opportunities for continuous improvement throughout the production cycle. So in the company Panduit of Costa Rica, in the area of ID & Molding is making efforts to obtain indicators that provide the information necessary for the progressive improvement of their production processes. Therefore, in order to further optimize production, the area has focused on obtaining indicators of availability, efficiency and yield. These parameters define an industry standard known as OEE (Operational Effectiveness and Efficiency). The OEE is obtained as the multiplication of the indicators of availability, efficiency and yield. However, this data is entirely dependent on the reliability indicators provide production process with respect to reality. For that reason, with the development of this project, will be able to obtain the necessary indicators to determine, in real time, the productivity of the production line. Also with this, you can generate a history with relevant information for the supervisors of the process. And with that, go continuously improving indicators based on substantiated data collection made solutions.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica ) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Electromecánica, 2014.
Keywords: Producción; Eficiencia; Efectividad Operacional; OEE; Rendimiento